Market Basket And Time Series Analysis: Case Study PT XYZ Sales Data - Wildan, Muhammad; Rizieq Hentihu, Moh Thaha; Jayadi, Riyanto (Cerdika: Jurnal Ilmiah Indonesia, 2025)
PT. XYZ is a retail company that has been operating since 2015 in New York, which seeks to increase sales through attractive package bidding strategies and ensuring stock availability for the following month’s highest-selling items. The project aims to analyze and forecast the items that will have the highest sales as well as provide package recommendations that can increase sales. The analysis was carried out using a machine learning model, with the Market Basket Analysis (MBA) method for package recommendations and the Auto Regressive Integrated Moving Average (ARIMA) for sales predictions. The results of the analysis show that the "USB-C Charging Cable" and "Bose SoundSport Headphones" have a strong association with the "Vareebadd Phone", which indicates the potential for increased sales if offered together. In addition, ARIMA’s predictions suggest that the MacBook Pro Laptop will generate the highest revenue, with an average projection of around 788,067.45. Based on these findings, we recommend PT. XYZ is preparing a package offering for the Vareebadd Phone with USB-C Charging Cable and Bose SoundSport Headphones, as well as preparing stock for the MacBook Pro Laptop, to meet market demand and maximize revenue potential.